Pendampingan IKM dalam Ecoprinting dan Digital Marketing: Indonesia - Miranda, Suci; Hidayat, Arif; Sari, Amarria Dila (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
The Ayu Arimbi SME, which is a batik craftsman in Sleman, has experienced a decrease in revenue due to a reduction in the number of products purchased by consumers, as the products offered are not sufficiently varied. Additionally, Ayu Arimbi SME only accepts orders directly at the store or via WhatsApp and does not maximize the use of social media for promotion and digital marketing. The purpose of this community service is to support efforts to diversify products by developing and innovating eco-print products and to help Ayu Arimbi SME expand its marketing to reach more consumers through digital marketing via social media. This community service program includes training and practice in eco-printing, comprehensive digital marketing training, and counseling on goods and space management using the 5S method. The material related to goods and space management is also important for increasing SME productivity. All community service programs have been successfully implemented. The results of this service include direct training guidance at the SME and eco-print fabrics created by the participants during the training. It is hoped that the knowledge and skills provided will bring benefits such as increased revenue, capacity, and competitiveness of Ayu Arimbi SME.